ANTIBACTERIAL ACTIVITY OF STREPTOMYCES SP SH7 ISOLATED FROM CARDAMOM FIELDS OF WESTERN GHATS IN SOUTH INDIA - D. GEETHA RAMANI; T. VINOTH KUMAR (International Journal of Pharma and Bio Sciences, 2012)
One hundred and forty seven strains of actinomycetes were isolated from soil samples collected from cardamom fields at Western Ghats of South India. The antimicrobial activities of the isolated strains were studied by well diffusion method. Eighty-eight isolates exhibited antibacterial activity against the target test bacteria. The isolate Streptomyces sp Sh7 exhibited promising antibacterial activity against Gram positive and Gram-negative bacteria. Identification of the isolate up to genus level was done. Optimization of cultural conditions for antibiotic production by the isolate Sh7 was carried out. HPLC-DAD (High performance liquid chromatography-Diode Array Detector) analysis of the crude culture filtrate was performed to detect the presence of any known antibiotic compound. The antibiotic was found to be extracellular in nature. The culture filtrate was subjected to sequential solvent extraction. The antibacterial compounds were extracted using butanol and purified by Thin Layer Chromatography. The maximum absorption spectra of the purified antibacterial compounds were determined.